2001
DOI: 10.1086/323460
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Meningitis Due toAngiostrongylus cantonensisin a Returned Traveler: Case Report and Review of the Literature

Abstract: Angiostrongylus cantonensis, the rat lungworm, is the principal cause of eosinophilic meningitis worldwide, and the increase in world travel and shipborne dispersal of infected rat vectors has extended this parasite to regions outside of its traditional geographic boundaries. We report a case of eosinophilic meningitis due to A. cantonensis in a patient who recently returned from a trip in the Pacific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Clinical exploration revealed that A. cantonensis invading human CNS caused eosinophilic meningitis and meningoencephalitis, and resulted in a serial of neurological symptoms, including persistent headache, paresthesia or hyperesthesia, nuchal rigidity, seizure, cognitive dysfunction, ataxic gait, and even unconsciousness [ 10 18 ]. These neurological symptoms were also identified in animals with A. cantonensis infection, which obviously presented lessening of the spontaneous activity and dysfunction for symmetry, balance and coordination of movements in infected rodents [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical exploration revealed that A. cantonensis invading human CNS caused eosinophilic meningitis and meningoencephalitis, and resulted in a serial of neurological symptoms, including persistent headache, paresthesia or hyperesthesia, nuchal rigidity, seizure, cognitive dysfunction, ataxic gait, and even unconsciousness [ 10 18 ]. These neurological symptoms were also identified in animals with A. cantonensis infection, which obviously presented lessening of the spontaneous activity and dysfunction for symmetry, balance and coordination of movements in infected rodents [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, with increased globalism, this parasite has continued to spread to other parts of the world, including to the Americas, 4,1214 with cases often identified in travelers returning from regions where angiostrongyliasis is endemic. 1518 In the United States, angiostrongyliasis has been present in Hawaii since at least 1959. 19,20 However, recently, A. cantonensis has been found in both mollusk and rat hosts in the Gulf Coast region of the continental United States, 2123 and sporadic autochthonous cases have been identified in other areas as well.…”
Section: Introductionmentioning
confidence: 99%